Pengaruh Religiusitas, Kepercayaan , Lokasi, Dan Pelayanan Terhadap Minat Membayar Zakat - Safitri, Novia Dwi; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2021)
Zakat is one of the instruments to equalize income to reduce poverty. The potential for zakat in Indonesia, especially in East Java is very high, but this has not been offset by the realization of the collection. People tend to pay zakat directly to mustahiq. This study aims to determine whether there is an influence of religiosity, belief, location, and service on the interest of the people of East Java in paying zakat through BAZNAS. In this study, the method used is a qualitative approach with a measurement scale using a Likert scale and multiple linear regression analysis techniques. The results showed that the variables of religiosity, trust, and service did not affect the interest in paying zakat through BAZNAS partially. While the location variable affects people's interest in paying zakat through BAZNAS. Together or simultaneously the variables of religiosity, belief, location, and service affect the interest in paying zakat through BAZNAS.